Leading with strategic thinking: four ways effective leaders gain insight, drive change, and get results - Olson, Aaron K.; Simerson, Keith B. (Hoboken, 2015)
"Be a more effective leader with strategic thinking Leading with Strategic Thinking reveals what effective leaders do differently. Eschewing the one-size-fits-all leadership model, this helpful guide outlines four general leadership types and demonstrates how each type achieves success whether through personal vision, structured process, collaboration, or by empowering others. The authors identify the actions and skills that distinguish strategic leadership, drawn from interviews and focus groups with over three hundred leaders from around the world. Examples and case studies illustrate these concepts in action, and the provided reference materials steer readers toward more advanced information on this important topic. The disruptive forces of technology and globalization raise new challenges for leaders. This book is a manual that will help executives and aspiring leaders harness these forces and address the two central questions of strategic leadership: * How do the best leaders develop their strategy? * How do effective leaders drive strategic change? Becoming a strategic leader isn t about mimicking an icon. The most effective leaders seize opportunity in a way that consciously integrates environmental requirements, stakeholder expectations, and personal ability. Leading with Strategic Thinking shows what these leaders do, and gives anyone the tools to be a more strategic leader."